Clarifying the neural basis of obsessive compulsive disorder : a combined structural and functional magnetic resonance imaging study - Eng, Goi Khia (2019)
Obsessive-compulsive disorder (OCD) is a debilitating disorder with limited treatment efficacies. This could partly be attributed to inadequate knowledge of the neurobiological basis of the disorder. Even though OCD has a prevalence rate of 3% in Singapore, research in OCD is relatively lacking compared to other psychiatric conditions. Existing neuroimaging literature in OCD have commonly reported abnormalities within the fronto-striatal regions, and some studies also indicated the involvement of the cerebellum in the disorder. However, exact contributions of the cerebellum in OCD pathophysiology have been unexplored. This thesis aims to clarify the neural basis and examine aberrant neural activity involved in OCD pathophysiology. Four studies are presented in this thesis. Study 1 presents a meta-analysis to synthesize existing findings of differences in structural grey matter and executive-function task-related activations between OCD samples and controls. Results indicated group differences in frontal-thalamic and cerebellar grey matter, and task-related activations in the cingulate, parietal and caudate regions. These findings suggest probable involvement of regions beyond the cortico-striatal-thalamo-cortical (CSTC) circuitry in OCD pathophysiology. Findings from Study 1 set the stage for subsequent neural investigations...